2018
DOI: 10.12681/jhvms.15470
|View full text |Cite
|
Sign up to set email alerts
|

Levels of certain biochemical and oxidative stress parameters in cattle with Brucellosis

Abstract: ABSTRACT. The purpose of the present study was to determine concentrations of some biochemical parameters and oxidative stress levels in cattle with brucellosis. For this purpose, a study group included with 20 cattle with brucellosis and a control group with 10 clinically healthy cattle were used. Blood samples were collected into the tubes (with and without anticoagulant agent) from the Jugular vein of animals in each group. The reduced glutathione (GSH) in whole blood and levels of malondialdehyde (MDA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Various authors have used different methods and various samples, some experiments are missing valid data about the sample preparation and some papers even consider GSSG concentrations to be negligible. Sharma et al (2011) found low mean concentrations of GSH (94 ± 21 µmol/l for dry cows and 234 ± 37 µmol/l for fresh cows), but, in another paper (Bozukluhan et al 2017), much higher values of T-GSH (76.30 ± 3.61 mg/dl; recalculated 2 482 ± 118 µmol/l) in the full blood of healthy cows were found. Kaneko (1997) mentioned levels of GSH in cattle 2 890 ± 460 µmol/l, nevertheless there is no information concerning the method that was used.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Various authors have used different methods and various samples, some experiments are missing valid data about the sample preparation and some papers even consider GSSG concentrations to be negligible. Sharma et al (2011) found low mean concentrations of GSH (94 ± 21 µmol/l for dry cows and 234 ± 37 µmol/l for fresh cows), but, in another paper (Bozukluhan et al 2017), much higher values of T-GSH (76.30 ± 3.61 mg/dl; recalculated 2 482 ± 118 µmol/l) in the full blood of healthy cows were found. Kaneko (1997) mentioned levels of GSH in cattle 2 890 ± 460 µmol/l, nevertheless there is no information concerning the method that was used.…”
Section: Discussionmentioning
confidence: 89%
“…The relationships between glutathione and some infectious diseases have been documented over the last several years. Bozukluhan et al (2017) detected diminished levels of glutathione in cattle suffering with brucellosis. Uzlu et al (2016) mentioned a decrease in glutathione in bulls with foot and mouth disease (mentioned above).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some papers evaluating the concentration of glutathione in blood were published in recent years, using similar spectrophotometrical method with Ellman's reagent as a fluorescent detectable product but the authors evaluated only T-GSH. Bozukluhan et al (2017) found the mean values of 76.30 ± 3.61 mg/dl (recalculated 2482 ± 118 µmol/l) in whole blood of healthy cows. They considered the GSSG levels negligible.…”
Section: Discussionmentioning
confidence: 93%
“…During the course of disease reduced glutathione diminishes, and we did not find values for GSSG in affected animals. The results show that diseased animals can restore GSH levels while recovering from the disease (Bozukluhan et al 2017;El-Mandrawy and Alam 2018;Uzlu et al 2016). Kirbas et al (2014) measured GSH values similar to ours.…”
Section: Meanmentioning
confidence: 92%